The PRI holds the power in México. When he awoke, the dinosaur was still there - Verdoy, Alfredo (Razón y fe, 2018)
After twelve years of being the National Action Party in government, last December 1st the Institutional Revolutionary Party (PRI) took office. In this editorial we will discuss the reasons why PRI has returned to the presidency. Despite the economic boom and the increasingly social benefits, the Institutional Revolutionary Party won the last presidential election as a «continuation of a never lost power» and not as «a better future for all Mexicans».